Haplotype analysis of newly diagnosed Portuguese and Brazilian families with fibrinogen amyloidosis caused by the FGA p.Glu545Val variant - Tavares, Isabel (2020)
Background: Fibrinogen A alpha-chain (AFib) amyloidosis is an autosomal dominant disease with an endemic foci in the district of Braga, northern Portugal [1]. Among the 16 amyloidogenic mutations identified in the fibrinogen A alpha-chain gene (FGA) [2,3], the c.1634A > T (p.Glu545Val) mutation (rs121909612) is the most common and, so far, the only one identified in Portugal. A first study using three common polymorphisms showed a single haplotype, associated with the FGA p.Glu545Val mutation in Irish–American and Polish–Canadian kindreds [4]. However, the origin of this amyloidogenic variant in diverse regions and its migration in the different populations are still unclear. Therefore, we proceeded to a preliminary study using two FGA haplotype markers in newly identified Portuguese and Brazilian carriers to investigate the possibility of a common ancestor.